Pengaruh Media Power Point Berbasis Slidesgo Terhadap Minat Belajar Siswa Kelas XI IPA SMA Negeri 06 Bombana - Sari, Tri Maniarta; Risma, Risma; Erfina, Erfina; Ernawati, Ernawati; Pamungkas, Rahmania (STKIP HARAPAN BIMA, 2024)
This research aims to determine the effect of using slidesgo-based power point learning media on the learning interest of class XI Science students at SMA Negeri 06 Bombana. This research is quantitative research using a quasi-experimental model. The total population in this study was 36 students of class XI Science at SMA Negeri 06 Bombana. The sample used in this research was 36 students consisting of two classes, namely: the experimental class consisting of 19 students and the control class consisting of 17 students. The variables in this research are the dependent variable, namely student interest in learning and the independent variable is slidesgo-based power point media. The instrument used in this research was a questionnaire. The data analysis techniques used in this research are descriptive analysis and inferential analysis. Inferential analysis is independent sample T-Test. The research results showed that the experimental class obtained a percentage score of 87% in the high category, while the control class obtained a percentage score of 44% in the very low category. After calculating 36 experimental and control questionnaires, the independent sample T-Test test value was obtained with a significant value of 0.000 0.05. Based on the research results, it can be concluded that there is a significant influence on learning interest in the control class and experimental class